Association Between Smoking with a Molecular Profile of Breast Cancer: Smoking and molecular profile of breast cancer - Ferreira, Greetchen Borges de Campos Bólico; Ferreira , Ildo Borges de Campos Bolico; Geha, Jamile Ahmed Borges; Moraes, Maria Cecília Leite de; Meirelles, Luciano Amorim; Ferreira Pôrto, Elias (Archives of Breast Cancer, 2024)
Background: Female breast cancer is one of the causes of the highest cancer mortality and morbidity in the world. It is already known that there is a strong association between smoking and breast cancer. However, the association between smoking and tumor severity is not very clear. The objective of this study was to assess the severity of the breast tumor, using the tumor's molecular classification as a tool according to its immunohistochemical profile in smoking and non-smoking women. Methods: This is a longitudinal study in which 208 women with a diagnosis of breast cancer were followed for 17 months, 80 of whom were smokers and all underwent anatomopathological diagnosis by core biopsy and subsequent immunohistochemistry, followed by treatment indicated according to the type and the clinical staging of the tumor. The severity of the tumor was assessed by its molecular classification according to its immunohistochemical profile. Results: Smoking was associated with higher mortality. The tumor with the most severe immunohistochemical profile was found in younger smokers. 19.7% of smokers had a triple negative tumor and 10% of non-smokers. The age of female smokers with triple negative was 48.2 years and of non-smoking women was 52.6 years (p = 0.005). In 17 months of follow-up, mortality among smokers was 39.5% and for nonsmokers, 20%. Survival was statistically significantly lower among the group of smokers (p=0.01). Conclusion: smoking is associated with greater breast cancer severity, risk for cancer severity was OR 5.5 times higher for the smoking group survival was statistically significantly lower among the group of smokers